Young Adults' Perception and Concept of Psychological Well-being Through Physical Activity: A Photo-elicitation Study - Raquel Pérez-Ordás; Javier Piñeiro-Cossio; Leticia P. Mosteo-Chagoyen; Verónica Sierra-Sánchez, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
Today, psychological health is a significant health concern. For this reason, it has been deemed essential to investigate how physical activity (PA) and sports can enhance psychological well-being (PWB). Consequently, this study aims to examine and comprehend how young adults perceive PWB through PA. This study's sample consists of 34 participants between the ages of 23 and 28. All participants in this study responded to semi-structured questionnaires that included photo-elicitation as a research technique. Young adults perceived physical activity and sports as a place to cultivate their PWB by emphasizing personal development, life purpose, and social relationships. In addition, the data analysis produced new dimensions such as liberty, self-assurance, and personal equilibrium. This study provides further information that will assist policymakers and researchers in developing effective PWB and mental health promotion programs and strategies for young adults and adolescents.